La complessità nella speculazione: alcune considerazioni gnoseologiche ed etiche - Nunnari, Patrizia (B@belonline, 2022)
The recovery of a complex view of human cognitive, social and bodily capacities and of the relationship with the world has led the world of research in recent decades to initiate important reflections and methodological changes. The exact sciences have now redesigned their scientific criteria, overcoming the Cartesian body fracture with a systemic thought of the world. Some philosophies, through the recovery of the symbol, the narratives and a restorative ethic of sense attentive to the entirety of the human dimension, they are walking parallel to the sciences towards a syncretic vision of existence, embodied knowability and responsible action. The global challenges that socio-political and ecological crises require, require the adoption of an ecological thinking that brings out the plurality of viewpoints of observers in the sciences and the complexity of the aspects and relationships between objects and their contexts, to in order to develop a thinking capable of dealing with the urgent problems evoked by the UN Agenda 2030.